2000
DOI: 10.1063/1.1321790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gate leakage current on noise properties of AlGaN/GaN field effect transistors

Abstract: Articles you may be interested inThe effect of the gate leakage current fluctuations on noise properties of AlGaN/GaN heterostructure field effect transistors ͑HFETs͒ has been studied in conventional HFET structures and in AlGaN/GaN metal-oxide-semiconductor heterostructure field effect transistors ͑MOS-HFETs͒. The comparison of the noise properties of conventional AlGaN/GaN HFETs and AlGaN/GaN MOS-HFETs fabricated on the same wafer, allowed us to estimate the contribution of the gate current noise to the HFET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 11 publications
0
33
0
Order By: Relevance
“…However, GaN-based Schottky interfaces are known to suffer from unusually large leakage currents under reverse bias [1][2][3]. Excess leakage currents through a Schottky gate strongly affects, not only gate-control and power consumption, but also the noise performance in GaN-based FET devices as recently pointed out [4]. In spite of this, there have been only a few reports on the leakage properties of Schottky contacts in the reverse bias region.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, GaN-based Schottky interfaces are known to suffer from unusually large leakage currents under reverse bias [1][2][3]. Excess leakage currents through a Schottky gate strongly affects, not only gate-control and power consumption, but also the noise performance in GaN-based FET devices as recently pointed out [4]. In spite of this, there have been only a few reports on the leakage properties of Schottky contacts in the reverse bias region.…”
Section: Introductionmentioning
confidence: 97%
“…Pt, Au and Ag were used for Schottky contacts. Just prior to the vacuum deposition, the GaN surfaces were treated in NH 4 OH solution for 15 min at 50 o C. The detailed XPS analysis revealed that this treatment was very effective in reducing natural oxide components on GaN and AlGaN surfaces [7,8]. I-V measurements were done using HP 4156A semiconductor parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the gate leakage current should not contribute much to the output noise in these devices. [6][7][8] …”
Section: A Contribution To Noise From Gate Leakage Currentmentioning
confidence: 99%
“…Large leakage adversely affects operation, power consumption, noise and reliability of devices [3]. Because of this, many papers have tried to explain I-V characteristics with limited success.…”
Section: Introductionmentioning
confidence: 99%